QbD-based fabrication of transferrin-anchored nanocarriers for targeted drug delivery to macrophages and colon cells for mucosal inflammation healing - Zeeshan, Mahira; Ain, Qurat Ul; Sunny, Ahad; Raza, Faisal; Mohsin, Muhammad; Khan, Salman; Weigmann, Benno; Ali, Hussain (Biomaterials Science, 2022)
Colon mucosal inflammation attracts a plethora of immune cells with overexpressed surface receptors. Colon drug targeting can be aided by exploiting overexpressed cell surface receptors which improve drug site retention for an extended period. We developed Tofacitinib citrate (Tofa) loaded transferrin anchored PLGA nanocarriers (Tofa-P/tfr NCs) via the quality by design (QbD) approach for specific binding to the transferrin receptor (TFR-1/CD71) overexpressed on macrophages and colon epithelial cells. Nanocarriers were produced using a modified emulsion-evaporation method with a protein adsorption technique. The QbD-risk assessment method was adopted to screen the variables impacting the quality of nanocarriers, which were then optimized using the 3(3) Box-Behnken design of experiment (DOE). The obtained nanocarriers have the desired physicochemical properties, drug entrapment, tfr adsorption, stability, mucoadhesion, and sustained drug release pattern at pH 7.4 (colon pH). In vitro cell-based studies confirmed the cellular biocompatibility and considerable uptake of nanocarriers by colon and macrophage cells; the uptake was diminished by anti-CD71/TFR1 antibodies. Tofa-P/tfr NCs demonstrated good colon targeting potential in the dextran sulfate sodium (DSS) induced ulcerative colitis (UC) model. In vivo therapeutic efficacy against UC was established through restored morphological and histopathological scores, vascular integrity, antioxidant levels, hematological parameters, pro-inflammatory cytokine/marker levels, and microbial indices. Tofa-P/tfr NCs shut down the elevated STAT-1 and TFR-1 levels, demonstrating the enhanced efficacy of the encapsulated drug. Thus, the QbD-driven approach successfully developed Tofa-P/tfr NCs with good potential to mitigate mucosal inflammation by targeting colon and macrophage surface receptors.
CRIS-Team WoS Importer:2023-01-20